2015
DOI: 10.1016/j.porgcoat.2015.02.023
|View full text |Cite
|
Sign up to set email alerts
|

New anhydride/epoxy thermosets based on diglycidyl ether of bisphenol A and 10-undecenoyl modified poly(ethyleneimine) with improved impact resistance

Abstract: New dendritic modifiers have been synthesized by amidation of hyperbranched poly(ethylenimine) (PEIs) with 10-undecenoic acid to obtain hyperbranched polymers (HBPs) with different degree of modification. These HBPs have been used as toughness modifiers in a proportion of 10 and 20% in reference to the epoxy resin in diglycidyl ether of Bisphenol A (DGEBA) / methyltetrahydrophthalic anhydride (MTHPA) formulations. The curing process has been studied by dynamic scanning calorimetry and by rheometry, which allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…In order to improve the impact resistance of a material, it is important to introduce mechanisms that can contribute to energy dissipation, thereby impeding crack propagation. It has been demonstrated that the use of HBPs can effectively enhance the impact strength of epoxy materials . However, the addition of LP decreases the impact strength in comparison to the neat epoxy‐D400 formulation (100D400).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In order to improve the impact resistance of a material, it is important to introduce mechanisms that can contribute to energy dissipation, thereby impeding crack propagation. It has been demonstrated that the use of HBPs can effectively enhance the impact strength of epoxy materials . However, the addition of LP decreases the impact strength in comparison to the neat epoxy‐D400 formulation (100D400).…”
Section: Resultsmentioning
confidence: 97%
“…reported values of impact strength lower than 4 kJ/m 2 in epoxy thermosets modified with hyperbranched poly(ester‐amide)s. Flores et al . and Acebo et al . reported values lower than 10 and 4 kJ/m 2 , respectively, in epoxy networks modified with undecenoyl‐modified hyperbranched polymers.…”
Section: Resultsmentioning
confidence: 99%
“…The synthetic process is carried out in one pot and two steps: first, the activation of 10-undecenoic acid by reaction with CDI and then the nucleophilic substitution of imidazole group in the CDI derivative by amines of the PEI structure. On changing the proportion of CDI and 10-undecenoic acid to NH reactive groups, different modification percentages could be obtained [165].…”
Section: Modification Of Hyperbranched Pei With Long Alkyl Chains Andmentioning
confidence: 99%
“…Epoxy resin (EP) is a kind of polymer which contains two or more epoxy groups in its molecular chain and forms thermosetting products through various reactions between epoxy groups. It has the advantages of high mechanical strength [1], high bonding strength [2], low shrinkage [3], high stability [4,5], and easy deployment and construction. However, epoxy resin has the disadvantages of poor toughness, brittle quality, easy cracking, and low impact strength, which results in limitations to its application to repairing concrete cracks.…”
Section: Introductionmentioning
confidence: 99%